Konseling Islam Melalui Terapi Berpikir Positif untuk Mengelola Stres Ketua Himpunan dan Organisasi - Rasyadi, Ahmad Fitra; Wardana, Mustahar Ali (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
This research aims to determine the process and results of Islamic Counseling through Positive Thinking Therapy to Manage Stress for the General Chair of HMP and UKM at the Faculty of Da'wah and Communication (FDK) Islamic State University of Sunan Ampel  Surabaya (UINSA). This problem was answered by researchers using qualitative research methods by case study analysis general chairs of HMP and UKM at FDK UINSA. The analysis used observation and interview techniques. The counseling process used cognitive restructuring to manage stress of the general chairs of HMP and UKM by changing negative perceptions into positive using thought records. The results of positive thinking therapy showed that there was a change in the connotation of negative thoughts which have been successfully transferred into positive thoughts by the counselee untill can suppress stress due to problems that arise and are felt by the counselee.